Histomorphometric analysis of orthodontically induced root resorption - K Tahir , Dalia (Mustansiria Dental Journal, 2004)
This clinical and histological investigation was designed to study the association between orthodontically applied force and related root resorption ni fortyeight adult patients where their treatment involved bilateral maxillary first premolar extraction which was postponed to use the 96 teeth as a test and control for the experiment. The patients were assigned ot one of six groups; the right premolars were moved buccaly using continuous, wel controlled, different forces range (30-80 grams) for ten weeks while the left premolars served as a control. By the end of het experimental period, the tecth were extracted and underwent routine histological preparations. Sections were tested using the image analysis computer system. Statistical analysis of the result revealed a non significant diflerence ni the mean vaule of resorbed area between hte control group and those ni which forces of 30, 40, 50 and 60 grams were used but a significant diference ni the mean value of groups ni which 70 and 80 grams were used. Regarding the depth of resorption a non significant difference was found ni hte mean value between the control groups ni which forces of 30, 40 gram were used but a significant difference was found ni groups in which forces of 50, 60, 07 and 80 gram used. Finally, the mean value of the resorbed aren and its depth were always more ni the palatal root than the buccal root and ni the apical third than the cervical third for all groups